Re-examination of Tai Chi culture under the phenomenon of "Creolization" - Zhang, Yao (The Journal of the International Society of Chinese Health Practices, 2021)
With the acceleration of the process of globalization, the phenomenon of cultural globalization has become a normalized phenomenon in today’s society. The fusion and interaction of foreign and local cultures have formed the so-called "Creolization" of the cultural status quo. This has had a certain impact on the development of local culture. Tai Chi culture, as a label of China’s excellent traditional culture, is also greatly affected by the wave of global cultural shocks, as a special cultural carrier of body narrative types, Derived from two different changes, one is based on the rules and standardization of competitive Tai Chi, based on the concept of Western sportsmanship, and the other is the re-nationalized Tai Chi, which traces the origin to the culture. This article firstly proposes whether the development of competitive Taijiquan under the influence of globalization conforms to the path of the development of Taiji culture through the method of literature and materials, and at the same time analyzes the current development situation of Taiji culture based on the influence of the phenomenon of "Creole". And how to pass it on. The article first summarizes the elegance of Tai Chi culture and the embodiment of Tai Chi culture in Tai Chi movements through the literature data, all showing the summary of Chinese culture and the constraints on the principles of life, and then concludes that Tai Chi culture is a summary of excellent traditional Chinese culture. The formation of the crystallization of wisdom with inheritance and continuity also shows that Tai Chi culture is an inevitable product of the development of Chinese traditional culture to a certain stage. Next, the perspective turns to the impact of the development of competitive sports on Tai Chi culture, and the analysis of the development of competitive Tai Chi at the current stage draws the conclusion that competitive Tai Chi draws lessons from the standardization and standardization of competitive sports, and the movements draw lessons from "high, difficult, new and beautiful." In the development direction of "innovation and innovation", the action specifications have gradually lost their unique taste to satisfy people’s appreciation. However, with the improvement of athletes’ physical fitness, the so-called competitive development has gradually lost the unpredictable results of competitive sports. The charm has led to a bottleneck in the development of competitive Tai Chi. The display of Tai Chi culture is gradually consumed by the athletes’ performance, and at the same time it has failed to achieve competitive development, and it is extended to conclude that this development method of giving up the original and the last has a certain effect on the Tai Chi culture. However, the way of exposing Tai Chi in a different way is worthy of recognition. Tai Chi has gradually come into people’s field of vision and has become one of the popular sports, but it only stays in sports and does not rise to the so-called culture. Level. So, has the development of Tai Chi culture really been developed in such a "weaning" manner? I then returned to analyze the status quo of Tai Chi culture under the influence of the phenomenon of "Creoleization". Through literature review, I found that although traditional Tai Chi rarely appears in competitions at this stage, it appears to be shining among the folks and the cultural heritage. There is still no end. Special colleges set up by universities, special martial arts research bases set up by the private sector, and the continuous appearance of Tai Chi in film and television dramas have injected fresh blood into the inheritance of Tai Chi culture. "Creoleization" phenomenon, the impact on Taijiquan is not blind invasion and assimilation. It is a cultural product that can last for thousands of years, and naturally has its strong vitality. Under this impact, Taiji culture is very much like these two completely opposites. The continuous development of the direction of competition, the road of competition, and the inheritance of folk culture. Later, I proposed to treat the influence of the phenomenon of "Creolization" on Taiji culture dialectically. Through literature reading and theoretical reference, I concluded that the phenomenon of "Creolization" actually did not cause serious damage to Taiji culture to a certain extent. The adverse effects have stimulated the development of Tai Chi culture to pursue a stronger "de-alienation". At the same time, it is concluded that the emergence of competitive Tai Chi is actually a cultural product based on cultural heritage and traditional Tai Chi, and there is no traditional Tai Chi culture. Without the support of Taijiquan, there would be no development of the two paths of Taijiquan and cultural inheritance, which led to the development of Taijiquan and Taichi culture to this day. Cultural inheritance has promoted the sustainable development of Taichi. In summary, the article proposes that the development of Taichi culture follows: The cyclical process of generation-collision-development-regeneration, the development of Tai Chi under the influence of "Creoleization" through competitive "removal of the opposite sex" to the development of "reserving the opposite sex" of re-culture is the reproduction of culture. Finally, the full text concludes that the phenomenon of Creole seems to be the erosion of globalization on itself, but in fact it is also a collision between culture and culture. It has a certain impact on Tai Chi culture and at the same time brings certain opportunities. Learn from each other’s strengths, and ensure that its own specificity will not be swallowed up by the torrent of globalization. The spread and continuation of any kind of culture and civilization must always maintain its roots and make the correct use of "Creolization". The influence of the phenomenon will continue to conform to the trend in the development process, and Tai Chi culture will surely be continued and inherited. In fact, whether it is competitive Tai Chi or traditional Tai Chi, as mentioned above, it is actually a "removal of the opposite sex" and "reserving the opposite sex". Two opposites, their common development actually also promotes the inheritance of Tai Chi culture. To make good use of the duality brought about by the phenomenon of "Creoleization", the development of Tai Chi culture will definitely move forward towards a higher level of civilization.